Work Stress on Burnout: The Mediating Role of Resilience - Habibullah, Takbiiratul; Sarianti, Rini (Human Resource Management Studies, 2023)
This study analyzes (1) the effect of work stress on burnout in nurses at Madina Bukittinggi Hospital (2) the effect of work stress on resilience in nurses at Madina Bukittinggi Hospital (3) the effect of resilience on burnout in nurses at Madina Bukittinggi Hospital (4) the effect of work stress on burnout through resilience in nurses at Madina Bukittinggi Hospital. This research is a causal research. The population of this study were all nurses at Madina Bukittinggi Hospital. The number of samples used was the total population of 64 people taken using total sampling. Data collection using a questionnaire with a Likert Scale. The analysis technique used through SmartPLS 4 software. The results of data processing in this study indicate that: (1) work stress has a positive and significant effect on burnout in nurses at Madina Bukittinggi Hospital (2) work stress has a negative and significant effect on resilience in nurses at Madina Bukittinggi Hospital (3) resilience has a negative and significant effect on burnout in nurses at Madina Bukittinggi Hospital (4) resilience mediates the effect of work stress on burnout in nurses at Madina Bukittinggi Hospital.